A Novel Copper Tape Wideband Wearable Antenna for Wban Application (International Journal of Innovative Research in Engineering & Management, 2022)
The compact antenna for on-body  applications is designed for covering ISM frequency  bands. The antenna covering ISM frequency bands in  range of 2.45 and 5.8 GHz. The circular structure with  triangular slots is responsible for obtaining the dual band  applications. The antenna designed on flexible polyimide  substrate having dielectric constant of 3.5 with loss  tangent of 0.008. The bending analysis of the antenna is  performed to analyze the flexible nature. The proposed  antenna covering the frequency range 2.3-3.5 GHz and  5.1-6.8 GHz with fractional bandwidth of 41% and 28%.  The antenna provides the stable dipole and omni  directional patterns. The measured antenna provides the  peak gain of 2.3 dBi at 2.5GHz and 4.7 dBi at 5.8 GHz  radiation efficiency of 78% at 2.5 GHz and 84% at 5.8  GHz. To validate the antenna performance antenna  undergone for the comparison of simulated and measured  results by placing antenna on human body.
Keywords: SAR; On-body applications; Circular Ring